2023
DOI: 10.1161/strokeaha.122.041660
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Between Clinical Trial Evidence and Actual Practice in Use of Dual Antiplatelet Therapy After Transient Ischemic Attack and Minor Stroke

Abstract: BACKGROUND: Randomized controlled trials (RCTs) proved that short-term (21–90 days) dual antiplatelet therapy (DAPT) reduces the risk of early ischemic recurrences after a noncardioembolic minor stroke or high-risk transient ischemic attack (TIA) without substantially increasing the hemorrhagic risk. We aimed at understanding whether and how real-world use of DAPT differs from RCTs. METHODS: READAPT (Real-Life Study on Short-Term Dual Antiplatelet Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Study methodology has been previously reported 13 and is briefly summarized in the following S3) have enrolled all consecutive patients treated with DAPT. The enrolment closed on 28 th February 2023.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study methodology has been previously reported 13 and is briefly summarized in the following S3) have enrolled all consecutive patients treated with DAPT. The enrolment closed on 28 th February 2023.…”
Section: Methodsmentioning
confidence: 99%
“…Study methodology has been previously reported 13 and is briefly summarized in the following sections. READAPT (NCT05476081) is an observational prospective multicenter real-world study, which included a baseline observation (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations